Beyond Blurred Lines : Rape Culture in Popular Media. - Phillips, Nickie D. (Rowman & Littlefield Publishers, 2016)
Beyond Blurred Lines explores the ways that the concept of "rape culture" resonates in popular media. This book demonstrates that popular culture, mass media, and social media are prominent sites for understanding and responding to sexual violence.